Stess Dependance of the Yield Surface for Gulf of Mexico Mudrock - Lambert, Stephen. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Civil Engineering.; Advisor: John Germaine.; Committee: Richard Plumb, and Luis Dorfmann.; Keywords: Geophysical engineering, Geological engineering, and Geotechnology.